2015
DOI: 10.1093/nar/gkv717
|View full text |Cite
|
Sign up to set email alerts
|

Sources of PCR-induced distortions in high-throughput sequencing data sets

Abstract: PCR permits the exponential and sequence-specific amplification of DNA, even from minute starting quantities. PCR is a fundamental step in preparing DNA samples for high-throughput sequencing. However, there are errors associated with PCR-mediated amplification. Here we examine the effects of four important sources of error—bias, stochasticity, template switches and polymerase errors—on sequence representation in low-input next-generation sequencing libraries. We designed a pool of diverse PCR amplicons with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
236
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(239 citation statements)
references
References 32 publications
2
236
0
1
Order By: Relevance
“…Prior to sequencing, many sample preparation workflows employ DNA amplification, particularly the Polymerase Chain Reaction (PCR). Consequently, errors that arise during PCR lead to false positive mutations and can obscure sequencing results, making it especially challenging to identify rare genetic variation [2]. In addition, the inherently high error rate of next-generation sequencing technologies requires additional steps to distinguish true mutation events from sequencing errors and is an active area of research [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to sequencing, many sample preparation workflows employ DNA amplification, particularly the Polymerase Chain Reaction (PCR). Consequently, errors that arise during PCR lead to false positive mutations and can obscure sequencing results, making it especially challenging to identify rare genetic variation [2]. In addition, the inherently high error rate of next-generation sequencing technologies requires additional steps to distinguish true mutation events from sequencing errors and is an active area of research [36].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that recombinants can also arise between complementary strands, or even during a single round of polymerase extension [22]. The rate of PCR-mediated recombination by polymerases has been studied by a phenotypic assay and next-generation sequencing, but has yet to be directly assayed by single-molecule sequencing methods [2, 23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, template concentration, bias against high GC templates, template switching, and polymerase errors may contribute to errors in downstream steps [2729]. These previous studies indicated that these bias and errors can be minimized by using the minimum number of amplification cycles required to form products and defining the optimal template concentration in the PCR reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in hybridization efficiency during capture, due to GC content variation in the genome, account for the poor coverage of some target exon regions. DNA regions with nucleotide repeats may also result in coverage problems (19, 20). Pseudogenes, as for IKBKG and NCF1 , also hamper correct data generation.…”
Section: Generating Next Generation Sequencing Datamentioning
confidence: 99%